Intravenous Administration of Bone Marrow-Derived Mesenchymal Stem Cell, but not Adipose Tissue-Derived Stem Cell, Ameliorated the Neonatal Hypoxic-Ischemic Brain Injury by Changing Cerebral Inflammatory State in Rat - Sugiyama, Yuichiro; Sato, Yoshiaki; Kitase, Yuma; Suzuki, Toshihiko; Kondo, Taiki; Mikrogeorgiou, Alkisti; Horinouchi, Asuka; Maruyama, Shoichi; Shimoyama, Yoshie; Tsuji, Masahiro; Suzuki, Satoshi; Yamamoto, Tokunori; et al. (Frontiers in Neurology, 2018)
Perinatal hypoxic-ischemic (HI) brain injury occurs in 1 in 1000 live births and remains the main cause of neurological disability and death in term infants. Cytotherapy has recently emerged as a novel treatment for tissue injury. In particular, mesenchymal stem cells (MSCs) are thought to have therapeutic potential, but little is known about the differences according to their origin. In the current study, we investigated the therapeutic effects and safety of intravenous injection of allogeneic bone marrow-derived MSCs (BM-MSCs) and adipose-derived stemcells (ADSCs) in a rat model of HI brain injury. HI models were generated by ligating the left carotid artery of postnatal day 7 Wistar/ST rats and exposing them to 8% hypoxia for 60 min. Bone marrow and adipose tissue were harvested from adult green fluorescent protein transgenic Wistar rats, and cells were isolated and cultured to develop BM-MSCs and ADSCs. At passaging stages 2–3, 1 × 105 cells were intravenously injected into the external right jugular vein of the HI rats at 4 h or 24 h after hypoxia. Brain damage was evaluated by counting the number of cells positive for active caspase-3 in the entire dentate gyrus. Microglial isotypes and serum cytokines/chemokines were also evaluated. Distribution of each cell type after intravenous injection was investigated pathologically and bio-optically by ex vivo imaging (IVIS®) with a fluorescent lipophilic tracer DiR. The mortality rate was higher in the ADSC group compared to the BM-MSC group, in pups injected with cells 4 h after hypoxia. The number of active caspase 3-positive cells significantly decreased in the BM-MSC group, and the percentage of M1 microglia (a proinflammatory isotype) was also lower in the BM-MSC vs control group in the penumbra of the cortex. Moreover, BM-MSC administration increased anti-inflammatory cytokine and growth factor levels, while ADSCs did not. Each injected cell type was mainly distributed in the lungs and liver, but ADSCs remained in the lungs longer. Pathologically, pulmonary embolisms and diffuse alveolar hemorrhages were seen in the ADSC group. These results indicated that injection of allogeneic BM-MSCs ameliorated neonatal HI brain injury, whereas ADSCs induced severe lung hemorrhage and higher mortality.